# Extensions 1→N→G→Q→1 with N=C3×C6 and Q=C3×Q8

Direct product G=N×Q with N=C3×C6 and Q=C3×Q8
dρLabelID
Q8×C32×C6432Q8xC3^2xC6432,732

Semidirect products G=N:Q with N=C3×C6 and Q=C3×Q8
extensionφ:Q→Aut NdρLabelID
(C3×C6)⋊(C3×Q8) = C6×PSU3(𝔽2)φ: C3×Q8/C3Q8 ⊆ Aut C3×C6488(C3xC6):(C3xQ8)432,757
(C3×C6)⋊2(C3×Q8) = C2×He33Q8φ: C3×Q8/C4C6 ⊆ Aut C3×C6144(C3xC6):2(C3xQ8)432,348
(C3×C6)⋊3(C3×Q8) = C6×C322Q8φ: C3×Q8/C6C22 ⊆ Aut C3×C648(C3xC6):3(C3xQ8)432,657
(C3×C6)⋊4(C3×Q8) = C2×Q8×He3φ: C3×Q8/Q8C3 ⊆ Aut C3×C6144(C3xC6):4(C3xQ8)432,407
(C3×C6)⋊5(C3×Q8) = C3×C6×Dic6φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6):5(C3xQ8)432,700
(C3×C6)⋊6(C3×Q8) = C6×C324Q8φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6):6(C3xQ8)432,710

Non-split extensions G=N.Q with N=C3×C6 and Q=C3×Q8
extensionφ:Q→Aut NdρLabelID
(C3×C6).(C3×Q8) = C3×C2.PSU3(𝔽2)φ: C3×Q8/C3Q8 ⊆ Aut C3×C6488(C3xC6).(C3xQ8)432,591
(C3×C6).2(C3×Q8) = C62.19D6φ: C3×Q8/C4C6 ⊆ Aut C3×C6144(C3xC6).2(C3xQ8)432,139
(C3×C6).3(C3×Q8) = C62.20D6φ: C3×Q8/C4C6 ⊆ Aut C3×C6144(C3xC6).3(C3xQ8)432,140
(C3×C6).4(C3×Q8) = C3×Dic3⋊Dic3φ: C3×Q8/C6C22 ⊆ Aut C3×C648(C3xC6).4(C3xQ8)432,428
(C3×C6).5(C3×Q8) = C3×C62.C22φ: C3×Q8/C6C22 ⊆ Aut C3×C648(C3xC6).5(C3xQ8)432,429
(C3×C6).6(C3×Q8) = C4⋊C4×He3φ: C3×Q8/Q8C3 ⊆ Aut C3×C6144(C3xC6).6(C3xQ8)432,207
(C3×C6).7(C3×Q8) = C4⋊C4×3- 1+2φ: C3×Q8/Q8C3 ⊆ Aut C3×C6144(C3xC6).7(C3xQ8)432,208
(C3×C6).8(C3×Q8) = C2×Q8×3- 1+2φ: C3×Q8/Q8C3 ⊆ Aut C3×C6144(C3xC6).8(C3xQ8)432,408
(C3×C6).9(C3×Q8) = C9×Dic3⋊C4φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6).9(C3xQ8)432,132
(C3×C6).10(C3×Q8) = C9×C4⋊Dic3φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6).10(C3xQ8)432,133
(C3×C6).11(C3×Q8) = C18×Dic6φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6).11(C3xQ8)432,341
(C3×C6).12(C3×Q8) = C32×Dic3⋊C4φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6).12(C3xQ8)432,472
(C3×C6).13(C3×Q8) = C32×C4⋊Dic3φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6).13(C3xQ8)432,473
(C3×C6).14(C3×Q8) = C3×C6.Dic6φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6).14(C3xQ8)432,488
(C3×C6).15(C3×Q8) = C3×C12⋊Dic3φ: C3×Q8/C12C2 ⊆ Aut C3×C6144(C3xC6).15(C3xQ8)432,489
(C3×C6).16(C3×Q8) = C4⋊C4×C3×C9central extension (φ=1)432(C3xC6).16(C3xQ8)432,206
(C3×C6).17(C3×Q8) = Q8×C3×C18central extension (φ=1)432(C3xC6).17(C3xQ8)432,406
(C3×C6).18(C3×Q8) = C4⋊C4×C33central extension (φ=1)432(C3xC6).18(C3xQ8)432,514

׿
×
𝔽